INVESTIGATION OF INFECTIOUS LARYNGEOTRACHEITIS VIRUS IN IRAQI CHICKEN FARMS - Aida Bara Allawe; Shony M.Odisho; Salameh Barhoom (Basrah Journal of Veterinary Research)
Twenty samples of Laryngeal and Tracheal tissues from laying chickens of two flocks with suspicious infectious laryngeotracheitis were tested for the detection of the causative virus by using virus isolation in chicken embryo fibroblast (CEF)cell culture and chicken embryos by chorioallantoic membrane inoculation and conventional polymerase chain reaction(PCR).The virus was isolated from three samples (larynx and trachea) out of ten samples at Al-Sawara city on (CEF)cell culture and produce pock lesions on chorioallantoic membrane of infected chicken embryos in which the virus was isolated. Positive PCR results were detected in the three clinical samples, isolated virus in CEF cell culture and isolated virus in chicken embryos (inoculated on chorioallantoic membrane).